Cerebrospinal fluid study in paraneoplastic syndromes. Issue 1 (25th March 2009) - Psimaras, D; Carpentier, A F; Rossi, C; ,
Abstract : Objective: Paraneoplastic neurological syndromes (PNS) probably result from an immune reaction against antigens shared by the nervous system and tumour cells. To characterise CSF alterations in these syndromes, we studied a large series of paraneoplastic patients. Methods: Using the PNS European database which includes patients diagnosed with PNS in Europe, we reviewed the clinical data of all patients included between 2000 and 2007 for which information on CSF was available. Patients were studied if they met the following inclusions criteria: (1) definite paraneoplastic disease with anti-Hu, anti-Yo, anti-CV2, anti-Ri anti-Ma/Ta and anti-Tr antibodies; (2) clinical information available; and (3) at least one CSF study. Results: 295 patients met the inclusion criteria. Abnormal CSF (pleiocytosis and/or high protein level and/or oligoclonal bands) was found in 93% of patients. Pleiocytosis, but not hyperproteinorachia, was more frequently seen in patients in whom the CSF study was done early in the evolution. In 24 patients, oligoclonal bands were the only abnormality found in the CSF (10%). Elevated numbers of cells were found in 47% of patients before the third month compared with 28% after the third month (p<0.01). This evolution might suggest a subacute inflammation phase within the nervous system, followed by a non-inflammatory phase. The inflammation profile was similar in all antibody types, cancers or neurological syndromes of the PNS. Surprisingly, anti-Hu patients with high pleiocytosis at the time of diagnostic had a better survival in this study than those without pleiocytosis (572 days vs 365 days; p = 0.05). Conclusion: CSF inflammation is a common finding in PNS patients and can be a helpful tool for diagnosis, especially if this analysis is done within 3 months after neurological onset.